Levels of certain biochemical and oxidative stress parameters in cattle with Brucellosis - BOZUKLUHAN, K.; MERHAN, O.; CELEBI, O.; BUYUK, F.; OGUN, M.; GOKCE, G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The purpose of the present study was to determine concentrations of some biochemical parameters and oxidative stress levels in cattle with brucellosis. For this purpose, a study group included with 20 cattle with brucellosis and a control group with 10 clinically healthy cattle were used. Blood samples were collected into the tubes (with and without anticoagulant agent) from the Jugular vein of animals in each group. The reduced glutathione (GSH) in whole blood and levels of malondialdehyde (MDA) and nitric oxide (NO) were determined spectrophotometrically. Additionally, aspartate aminotransferase (AST), alanine aminotransferase (ALT), urea, creatinine and iron (Fe) levels in serum samples were colorimetrically determined. Compared with the animals in the control group, it was determined that cattle with brucellosis had significantly (P<0.01) higher levels of AST, ALT, creatinine and NO and lower level of Fe. The increases of MDA and GSH levels were moderate and significantly important (P<0.05) while serum urea manner was not significantly altered. It was determined that significant alterations occurred in various biochemical parameters and antioxidant activity decreased in cattle with brucellosis.